Effect of Cutting System and Time of Nitrogen Application on Forage Yield of Barley - Mohamed, Moataz Ali; Khair, Mohammed A. M. (University of Khartoum Journal of Agricultural Sciences, 2025)
An experiment was conducted at Hudeiba Research Station Farm during the winter seasons of 2004/05, 2005/06 and 2006/07 to study the effect of cutting system and time of nitrogen application on forage yield of barley. The experiment was executed in split plot design with three replications; the times of nitrogen application were assigned to the main plots and the cutting systems to the subplots. Four nitrogen applications: at sowing, 15, 30 and 45 days from sowing (DAS) and four cutting systems: a single cut of the primary crop (SC) and three double cuts referred to as DC1, DC2 and DC3 were studied. The primary crops of the SC were cut at the milk stage, while those of the double cuts were cut at the age of 30, 45 and 60 DAS for DC1, DC2 and DC3, respectively, and the secondary cut in each double cut was at the milk stage. Compared with the SC system, the three DC systems prolonged the growing season but significantly reduced the dry matter yields even in the cumulative of both cuts. The DC systems increased the tiller densities, but reduced the plant densities and the total culm densities of the secondary crops. In terms of the cumulative yields of the DC systems, DC1outyielded the other DC systems. The time of nitrogen application did not affect the forage yield.